Be a great problem solver–Now! : the 2-in-1 manager: speed read–instant tips, big picture–lasting results /: the 2-in-1 manager: speed read–instant tips, big picture–lasting results. (2016) - Reed, Adrian Paul, 1981-
No abstract available